Numerical modelling of the hydrodynamics driven by tidal flooding of the land surface after dyke breaching - Rachel A. Burns; Ryan P. Mulligan; Megan Elliott; Danika van Proosdij; Enda Murphy (Nature-Based Solutions)
Managed dyke realignment is a method of creating more coastal wetland environments, by breaching constructed dykes (levees) to allow seawater driven by tides to flood the land surface and enable re-establishment of salt marshes over time. However, coastal land regions that are protected by dykes experience major hydrodynamic changes after breaching. To investigate these dynamics, a dyke in Atlantic Canada was purposefully breached and the adjacent land surface allowed to flood with the tides. Field measurements pre- and post-breach provide a rare opportunity to model the hydrodynamics of early dyke realignment in a hypertidal estuary in the Bay of Fundy. These include measurements of water levels and current velocities at spring tide collected across of field site. A numerical model with an unstructured flexible mesh (Delft3D-FM) was applied to examine the impacts of tidal flooding from a river channel, through the dyke breach and across the previously agricultural landscape that was historically a salt marsh. The model was used to simulate the hydrodynamics inside and around the breach before and after seawater flooding during spring tides, to evaluate the initial impacts of this nature-based method of managed dyke realignment. The results indicate that the breach was not wide enough to influence water levels within the Missaguash River. The depth-averaged current speeds can exceed 1 m s−1 within the breach and are typically <0.3 m s−1 across the flooded area with an average depth of 0.66 m over the simulation period with six tidal cycles. The model results also highlight the importance of high-resolution computational grids and variable bottom roughness for simulating the hydrodynamics of small-scale salt marsh restoration projects. Overall, the results may provide insight to researchers and practitioners in applying nature-based solutions to improve coastal resilience.